APPLICATION ON PREDICTING FATIGUE LIFE IN AIRCRAFT STRUCTURE BASED ON PHM TECHNOLOGY - SONG Bo; ZHU QingYu; ZENG ZhaoYang (Jixie qiangdu)
Fatigue failure of the airframe structure occurs almost in the hole position of the fastener hole,Structural fatigue fracture will lead to a catastrophic accident. PHM（ Prediction and Health Management） technology can be used to predict when fatigue failure may occur,thereby achieving self-service security and reducing the use and protection costs. Based on the failure physical model,the fatigue life prediction method of the joint is established in this paper. Firstly,the stress serious factor and the fatigue notch coefficient of the hole member are solved. Then,the elastic section of the strain-life curve is modified to make the local stress-which is suitable for the prediction of high and low cycle fatigue life. The results show that the error of the fatigue life prediction method is less than 17% compared with the fatigue test results,which shows the effectiveness of the proposed method.